Social Protection as the Fifth Estate: Dependency Policy in France - Arteaga, Eguzki (Cuadernos de Trabajo Social, 2012)
This article analyzes dependency policies in France. If the reforms carried out during the 2000s constitute the base of the policies of attention for dependency, they are still insufficient and will not allow facing an increase in needs. If a loss of autonomy has been developed and structured by the most recent reform of policies of attention, it has certain gaps and it will have to face a structural increase of social health needs. In this sense, the creation of a fifth risk offers the opportunity to realize a few structuring choices in terms of socialization of spending and of assembling the conditions for a suitable and efficient evolution in the offering of services to those concerned.
Keywords: Social policy; Dependency; Reform; France.